Genetic profile, metabolic syndrome and breast cancer risk in Kazakhstani women (Experimental biology, 2018)
The work is devoted to the study of the relationship of breast cancer with the metabolic syndrome and genes involved in the metabolism of lipids. In the framework of this study, we recruited 136 participants diagnosed with breast cancer and 83 conditionally healthy participants in the control group. Among the diseases associated with breast cancer, hypertension, chronic bronchitis, ischemic heart disease, uterine myoma, cholecystitis, varicose veins of the lower extremities, pancreatitis are prevalent. The incidence of type 2 diabetes was 13.2%. Biochemical analysis on 18 metabolic parameters showed that in the group of patients compared with the control group, the level of homocysteine and vitamin B12 is much higher than normal. Data analysis showed a high correlation between homocysteine levels and the risk of developing breast cancer (OR = 15.29, CI = 5.67-41.28, p